Does caring for grandchildren influence life satisfaction? A national-level analysis among older adults in India using a propensity score matching approach - Anukul Barman; Mihir Adhikary; Sunil Sarode (BMC Public Health)
Abstract Background In the Indian socio-cultural context, the involvement of older adults in grandchild care is a normative expectation and a common household practice. Despite its prevalence, limited empirical evidence exists on how such caregiving responsibilities affect the psychological well-being and life satisfaction of older individuals. This study addresses this gap by examining the association between grandchild caregiving and life satisfaction among older adults in India. Method This study draws upon nationally representative data from Wave 1 (2017–2018) of the Longitudinal Ageing Study in India (LASI), comprising 25,650 individuals aged 60 to 80 years. To examine the association between grandchild caregiving and life satisfaction among older adults, we employed Ordered Logistic Regression models to account for the ordinal nature of the outcome variable. Propensity Score Matching (PSM) was also applied to address potential selection bias and ensure comparability between caregivers and non-caregivers based on observed covariates. Results The analysis revealed a statistically significant positive association between grandchild caregiving and life satisfaction among older adults. Specifically, individuals engaged in grandchild care exhibited higher odds of reporting greater life satisfaction (OR = 1.16; 95% CI: 1.10–1.23). Findings from the PSM analysis further supported this relationship, with an average treatment effect (ATE) of 0.057, indicating that caregiving for grandchildren contributes meaningfully to enhanced life satisfaction in later life. Conclusion These findings underscore the positive role of grandchild caregiving in enhancing life satisfaction among older adults in India. Promoting supportive intergenerational relationships may therefore serve as an important strategy for improving psychological well-being in later life.